2012
DOI: 10.1093/cid/cis542
|View full text |Cite
|
Sign up to set email alerts
|

A Single Dose of Vero Cell-Derived Japanese Encephalitis (JE) Vaccine (Ixiaro) Effectively Boosts Immunity in Travelers Primed With Mouse Brain-Derived JE Vaccines

Abstract: The new Japanese encephalitis vaccine (JE-VC, Ixiaro) has replaced mouse brain–derived vaccines (JE-MB) associated with serious safety concerns. A single dose of JE-VC effectively boosted immunity in JE-MB–primed travelers. Current recommendations for booster vaccination should be reevaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…The same volunteers had been evaluated for their immune response against the 2 GIII vaccine strains in our previous study exploring the ability of a heterologous vaccine to boost JE immunity [8]. These vaccinees were now evaluated for the presence of neutralizing antibodies against 5 JEV strains representing genotypes I–IV.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same volunteers had been evaluated for their immune response against the 2 GIII vaccine strains in our previous study exploring the ability of a heterologous vaccine to boost JE immunity [8]. These vaccinees were now evaluated for the presence of neutralizing antibodies against 5 JEV strains representing genotypes I–IV.…”
Section: Methodsmentioning
confidence: 99%
“…Eligibility criteria for the study population have been described in detail previously [8]. Moreover, to avoid cross-reactions due to preexisting antibodies, participants found to be seropositive for 1 or more of the JEV test strains before vaccination (n = 5) were excluded from the final analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Another phase III trial 42 aimed to investigate the immunogenicity and safety of administering IXIARO to 1-3-year-old children in India (n D 60). 2 £ 6 mg and 2 £ 3 mg doses IXIARO delivered on days 0 and 28 were compared with 3 doses of JenceVac TM (inactivated mouse-brain derived vaccine).…”
Section: Resultsmentioning
confidence: 99%
“…Nakayama vs. Beijing-1 or SA14-14-2, or any of these vs. other wild-type G-III strains) with MBDI, SA14-14-2 LAV, JE-CV as well as Vero CCDI vaccines, although the differences in SCRs or GMTs are not significant statistically. 22,24,25,27,31,65,70,71,117,120,122,136,[165][166][167] This differential neutralization as well as protection against G-III viruses has also been shown in mouse challenge studies. 168 Other studies have shown no such differences or higher GMTs with the heterologous virus strains.…”
Section: Cross-reactivity and Cross-protection Of Antibody Responses mentioning
confidence: 96%
“…134 In 1-3-year-old children, this vaccine produced SCRs of 65%-71%, with no significant difference between 3 or 6 mg per dose, after one dose, and 95% after two doses, being equivalent to two or three doses, respectively, of the MBDI vaccine. 135 The vaccine could also boost responses earlier elicited by MBDI vaccine in Finnish and Swedish travelers, 136 as well as in US marines. 137 Another CCDI vaccine, but derived from the P-1 strain, 138 was demonstrated to be as immunogenic as the MBDI vaccine in a Phase I study in adults; SCR was 96.7% with this vaccine as compared to 92.9% with the MBDI vaccine, and GMTs were similar between the two vaccines after the first and the second dose, but higher for the CCDI vaccine after the third dose.…”
mentioning
confidence: 99%